Race effects on temporal summation to heat pain in youth. Issue 5 (May 2015) - Morris, Matthew C.; Walker, Lynn; Bruehl, Stephen; Hellman, Natalie; Sherman, Amanda L.; Rao, Uma
Abstract : Abstract: Racial differences in pain responsiveness have been demonstrated in adults. However, it is unclear whether racial differences are also present in youth and whether they extend to experimental pain indices assessing temporal summation of second pain (TSSP). Temporal summation of second pain provides an index of pain sensitivity and may be especially relevant in determining risk for chronic pain. This study assessed pain tolerance and TSSP to evoked thermal pain in 78 healthy youth (age range, 10-17), 51% of whom were African American and 49% were non-Hispanic white. Multilevel models revealed within-individual increases in pain ratings during the temporal summation task in non-Hispanic white youth that were consistent with TSSP. Pain ratings did not change significantly during the temporal summation task in African-American youth. Baseline evoked pain ratings were significantly higher in African-American compared with non-Hispanic white youth. These findings suggest that enhanced responsiveness to evoked thermal pain in African Americans is present in adolescence but is unlikely to be related to elevated TSSP. These results may have implications for understanding racial differences in chronic pain experience in adulthood. Abstract : Findings suggest that enhanced responsiveness to evoked thermal pain in African Americans is present in adolescence but is unlikely to be related to elevated temporal summation of second pain.